RANCANG BANGUN WEBSITE GENBI UNSIKA BERBASIS REACT DAN NODE.JS (EXPRESS) DENGAN PENDEKATAN AGILE - Rangga Mukti Daniswara; Nina Sulistiyowati; Apriade Voutama (Universitas Lampung, 2026)
The GenBI UNSIKA community requires a digital platform to support activity publication, information management, and scholarship registration more effectively. This study aims to implement the previous UI/UX design into a functional website using React for the frontend and Node.js (Express) for the backend with an Agile approach based on Extreme Programming (XP). The research stages include planning, design, coding, and testing. The results show that the website successfully provides public information pages, scholarship information and registration modules, and an admin/CMS dashboard for managing articles, activities, galleries, members, and applicant data. Black-box testing indicates that all core modules run according to the test scenarios, making the website more modern, centralized, and easier to manage